Impact of the COVID-19 Epidemic on Stroke Care and Potential Solutions - Zhao, Jing (Stroke, 2020)
BACKGROUND AND PURPOSE: When the coronavirus disease 2019 (COVID-19) outbreak became paramount, medical care for other devastating diseases was negatively impacted. In this study, we investigated the impact of the COVID-19 outbreak on stroke care across China. METHODS: Data from the Big Data Observatory Platform for Stroke of China consisting of 280 hospitals across China demonstrated a significant drop in the number of cases of thrombolysis and thrombectomy. We designed a survey to investigate the major changes during the COVID-19 outbreak and potential causes of these changes. The survey was distributed to the leaders of stroke centers in these 280 hospitals. RESULTS: From the data of Big Data Observatory Platform for Stroke of China, the total number of thrombolysis and thrombectomy cases dropped 26.7% (P<0.0001) and 25.3% (P<0.0001), respectively, in February 2020 as compared with February 2019. We retrieved 227 valid complete datasets from the 280 stroke centers. Nearly 50% of these hospitals were designated hospitals for COVID-19. The capacity for stroke care was reduced in the majority of the hospitals. Most of the stroke centers stopped or reduced their efforts in stroke education for the public. Hospital admissions related to stroke dropped ≈40%; thrombolysis and thrombectomy cases dropped ≈25%, which is similar to the results from the Big Data Observatory Platform for Stroke of China as compared with the same period in 2019. Many factors contributed to the reduced admissions and prehospital delays; lack of stroke knowledge and proper transportation were significant limiting factors. Patients not coming to the hospital for fear of virus infection was also a likely key factor. CONCLUSIONS: The COVID-19 outbreak impacted stroke care significantly in China, including prehospital and in-hospital care, resulting in a significant drop in admissions, thrombolysis, and thrombectomy. Although many factors contributed, patients not coming to the hospital was probably the major limiting factor. Recommendations based on the data are provided.